Carboxyl functionalized porous organic polymer adsorbent as well as preparation method and application thereof
By introducing carboxyl hydrophilic groups into the porous organic polymer LNU-80, LNU-80-COOH was prepared, which solved the problems of slow adsorption kinetics and low adsorption capacity of traditional adsorbents in water, and achieved efficient adsorption of water-soluble dyes and good cycle stability.
Patent Information
- Application Number
- CN202511348161.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-20
- Publication Date
- 2025-12-05
AI Technical Summary
Existing adsorbent materials such as activated carbon, zeolite and MOFs exhibit slow adsorption kinetics, low adsorption capacity and poor regeneration ability when removing pollutants from water, making it difficult to efficiently remove water-soluble dyes.
The porous organic polymer LNU-80 was synthesized via Friedel-Crafts coupling reaction, and carboxyl hydrophilic groups were introduced into the framework via alkalization reaction to prepare the carboxyl-functionalized porous organic polymer LNU-80-COOH. The adsorption performance was improved by utilizing its electrostatic interaction, hydrogen bonding and π-π interaction with cationic dyes.
LNU-80-COOH exhibits an adsorption capacity of up to 4375.9 mg g⁻¹ for malachite green at room temperature, demonstrating excellent adsorption selectivity and good cycling stability, making it suitable for the efficient removal of cationic dyes from water.
Smart Images

Figure CN121064427A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chemistry and new materials technology, specifically relating to a method for preparing a carboxyl-functionalized porous organic polymer adsorbent and its application in the field of dye wastewater. Background Technology
[0002] Clean and safe drinking water is crucial for humanity, yet a portion of the global population still suffers from freshwater scarcity. With industrial development, the emission of pollutants from chemicals and agriculture is rapidly increasing, constantly threatening human health. Among these, water-soluble dyes, due to their high stability, high toxicity, and non-biodegradability, are listed as one of the most dangerous pollutants, severely impacting human health and ecosystems. Therefore, developing an economical, efficient, and easily effective method for removing organic dyes is of great significance for environmental protection and water resource utilization. To date, scientists have developed various wastewater treatment technologies, such as chemical precipitation, membrane separation, ion exchange, solvent extraction, biological methods, electrochemical methods, and adsorption separation. Adsorption separation, with its advantages of strong anti-interference ability and low environmental pollution, is widely used to remove pollutants from water. Therefore, the selection of adsorbents is crucial for improving adsorption performance. Traditional adsorbent materials, such as activated carbon, zeolite, and metal-organic frameworks (MOFs), limit their application in wastewater pollutant removal due to slow adsorption kinetics, low adsorption capacity, and poor regeneration ability. Therefore, there is an urgent need to develop novel adsorbents for the efficient removal of pollutants from water.
[0003] Porous organic polymers (POPs), as a branch of porous materials, have attracted considerable attention from researchers due to their advantages such as high specific surface area, good stability, and easy functionalization of the framework. POPs possess a benzene-rich framework with π-π interactions with dye guests, and the introduction of hydrophilic functional groups can greatly improve the dispersibility of the adsorbent in water. Therefore, POPs exhibit highly efficient adsorption capacity for aromatic organic dyes. Based on this, we selected phenyl maleic anhydride and tetraphenylmethane as building blocks and designed and synthesized a porous organic polymer based on anhydrides, LNU-80, using a Friedel-Crafts coupling reaction. To address the highly hydrophobic framework of traditional POPs materials due to their benzene-rich structure, this invention performs post-modification of the polymer via an alkalization reaction, further introducing hydrophilic carboxyl groups into the framework to prepare a carboxyl-functionalized porous organic polymer, LNU-80-COOH. The presence of the modified hydrophilic groups effectively improves the water dispersibility of the original polymer and provides a large number of active sites. Experimental results show that LNU-80-COOH exhibits excellent adsorption performance for malachite green, with an adsorption capacity as high as 4375.9 mg g at room temperature. -1The high adsorption capacity may be attributed to the electrostatic interactions, hydrogen bonds, and π-π interactions between the carboxyl-rich functional groups in the polymer backbone and the cationic dye malachite green, as well as its good water dispersibility. In summary, this type of adsorbent material exhibits excellent adsorption selectivity and good cycling stability, and has broad development prospects in the field of dye wastewater treatment. Summary of the Invention
[0004] The purpose of this invention is to provide a novel design strategy for preparing a porous organic polymer based on acid anhydrides. By introducing hydrophilic groups through alkalization, the polymer's dispersibility in water is improved while providing numerous active sites, enabling its application as an adsorbent for the removal of the cationic dye malachite green from water. The synergistic effect of the carbonyl and hydroxyl groups in the LNU-80-COOH skeleton gives LNU-80-COOH a more stable high electronegativity, providing additional negatively charged active sites that can bind to the cationic dye malachite green through electrostatic interactions. In addition, there are π-π interactions between the polymer skeleton and hydrogen bonding interactions between hydroxyl groups and malachite green, thus effectively improving the adsorption performance of malachite green in water. The preparation method proposed in this invention is simple to operate, environmentally friendly, and widely applicable, providing an effective strategy for the targeted design of novel adsorbents for the efficient removal of pollutants in water.
[0005] To achieve the above objectives, a carboxyl-functionalized porous organic polymer adsorbent is provided, with the structural formula shown in formula (I).
[0006]
[0007] (I).
[0008] The preparation method of the above-mentioned carboxyl-functionalized porous organic polymer adsorbent includes the following steps: dissolving LNU-80 and NaOH in distilled water, heating the reaction mixture under reflux with constant stirring, cooling to room temperature, washing the obtained primary product several times, and vacuum drying to obtain a brownish-yellow powder as the carboxyl-functionalized porous organic polymer adsorbent LNU-80-COOH.
[0009] The preparation method of the above-mentioned carboxyl-functionalized porous organic polymer adsorbent, specifically LNU-80, is as follows:
[0010] Step 1: Under nitrogen atmosphere, add phenyl maleic anhydride and tetraphenylmethane to a double-necked flask;
[0011] Step 2: After three vacuum-nitrogen cycles, add dimethyl formaldehyde (FDA) and anhydrous 1,2-dichloroethane, and stir.
[0012] Step 3: After stirring, add anhydrous FeCl3 to initiate the reaction;
[0013] Step 4: After the reaction is complete, filter and wash several times to remove unreacted monomers and catalyst;
[0014] Step 5: The obtained solid product was extracted with tetrahydrofuran using a Soxhlet extractor and dried under vacuum to obtain a brownish-yellow powder, which was LNU-80.
[0015] In the above-mentioned method for preparing a carboxyl-functionalized porous organic polymer adsorbent, step 3 involves reacting at 45 °C for 5 h, followed by raising the temperature to 80 °C and reacting for 19 h.
[0016] In the above-mentioned method for preparing a carboxyl-functionalized porous organic polymer adsorbent, the heating and reflux is carried out at 100 °C for 24 h.
[0017] The above-mentioned application of a carboxyl-functionalized porous organic polymer adsorbent in the adsorption of the cationic dye malachite green.
[0018] The above application is carried out as follows: in a solution of malachite green, the pH is adjusted to 2-10, the above-mentioned carboxyl-functionalized porous organic polymer adsorbent LNU-80-COOH is added, and the malachite green is adsorbed by shaking at a temperature of 25-45 °C.
[0019] In the above application, the pH is adjusted to 10.
[0020] In the above application, the temperature is 45°C.
[0021] The beneficial results of this invention are:
[0022] 1) This invention introduces a large number of hydrophilic groups (-COOH) into an anhydride-based polymer backbone through post-modification, thereby preparing a carboxyl-functionalized porous organic polymer that exhibits excellent adsorption performance and good cycling stability for the cationic dye malachite green in water.
[0023] 2) The porous organic polymer adsorbent prepared in this invention exhibits high selective adsorption capacity for the cationic dye malachite green through hydrogen bonding, electrostatic interaction, π-π interaction and good water dispersibility.
[0024] 3) The raw materials used in this invention are inexpensive and readily available, the process is simple, and it is suitable for large-scale production, showing good development prospects in the field of wastewater treatment. Attached Figure Description
[0025] Figure 1 Infrared spectra of porous organic polymers LNU-80, LNU-80-COOH and their corresponding monomers.
[0026] Figure 2-1 Nitrogen adsorption-desorption curves of porous organic polymer LNU-80.
[0027] Figure 2-2 Nitrogen adsorption-desorption curves of porous organic polymer LNU-80-COOH.
[0028] Figure 3-1 Pore size distribution diagram of porous organic polymer LNU-80.
[0029] Figure 3-2 Pore size distribution diagram of porous organic polymer LNU-80-COOH.
[0030] Figure 4-1 : The effect of pH on the zeta potential of porous organic polymer LNU-80.
[0031] Figure 4-2 : Effect of pH on the zeta potential of porous organic polymer LNU-80-COOH.
[0032] Figure 5 Thermogravimetric spectra of porous organic polymers LNU-80 and LNU-80-COOH.
[0033] Figure 6-1 : Effect of pH on the adsorption performance of porous organic polymer LNU-80.
[0034] Figure 6-2 : Effect of pH on the adsorption performance of porous organic polymer LNU-80-COOH.
[0035] Figure 7-1 Adsorption isotherm of porous organic polymer LNU-80 for malachite green at 25 °C.
[0036] Figure 7-2 Adsorption isotherm of porous organic polymer LNU-80-COOH for malachite green at 25 °C.
[0037] Figure 8 Adsorption isotherms of porous organic polymer LNU-80-COOH for malachite green at 25 ℃, 35 ℃ and 45 ℃.
[0038] Figure 9 The effect of different ions on the adsorption of malachite green in water by the porous organic polymer LNU-80-COOH.
[0039] Figure 10 Effect of different salt concentrations on the adsorption of malachite green in water by porous organic polymer LNU-80-COOH.
[0040] Figure 11The porous organic polymer LNU-80-COOH affects the activity of malachite green (400 mg L) in different water bodies. -1 Adsorption capacity of ).
[0041] Figure 12 Cyclic stability study of porous organic polymer LNU-80-COOH. Detailed Implementation
[0042] The following are embodiments of the present invention, which are helpful for understanding the present invention, but the scope of protection of the present invention is not limited thereto.
[0043] Example 1: Synthesis of LNU-80, a porous organic polymer based on acid anhydrides
[0044] 1. Sample synthesis:
[0045] Under nitrogen atmosphere, phenyl maleic anhydride (1.24 mmol, 217 mg) and tetraphenylmethane (0.62 mmol, 200 mg) were added to a 100 mL double-necked flask. After three vacuum-nitrogen cycles, 0.19 mL of dimethylformaldehyde (FDA) and 30 mL of anhydrous 1,2-dichloroethane were injected into the reaction flask using a syringe. After stirring for 30 min, anhydrous FeCl3 (2.4 mmol, 404 mg) was added. The reaction was carried out at 45 °C for 5 h, and then the temperature was increased to 80 °C for 19 h.
[0046] 2. Sample post-processing:
[0047] After the reaction was complete, the primary product was filtered and washed several times with dichloromethane, methanol, and acetone to remove unreacted monomers and catalyst. The obtained solid product was extracted with tetrahydrofuran using a Soxhlet extractor for 72 h. The product was then dried under vacuum at 100 °C for 24 h to obtain a brownish-yellow powder, designated LNU-80.
[0048] Example 2 Synthesis of a carboxyl-functionalized porous organic polymer LNU-80-COOH
[0049] LNU-80 (0.205 mmol, 200 mg) and NaOH (65.76 mg, 1.644 mmol) were dissolved in 20 mL of distilled water. A round-bottom flask was connected to a reflux condenser, and the reaction mixture was heated to reflux (100 °C) with a PTFE-coated magnetic stir bar under constant stirring. After refluxing the reaction system for 24 h, it was cooled to room temperature, and the resulting primary product was washed several times with 1 M HCl, 10 mM dilute HCl, and H2O, respectively. The resulting product was further dried in a vacuum drying oven for 24 h to obtain a brownish-yellow powder, LNU-80-COOH.
[0050] The synthesis diagrams of the porous organic polymers LNU-80 and LNU-80-COOH prepared in this invention are shown below:
[0051]
[0052] Figure 1 : Figure 1 These are the infrared spectra of the porous organic polymers LNU-80 and LNU-80-COOH synthesized in this invention, and their corresponding monomers. The spectra show that LNU-80 exhibits a peak at 1680 cm⁻¹. -1 The C=O tensile vibration peak at 2917 cm⁻¹ and the peak at 2917 cm⁻¹ -1 The methylene stretching vibration was observed. The aforementioned peak value confirms the successful synthesis of LNU-80. After basic modification, a peak value was found at 3440 cm⁻¹. -1 The sharp infrared absorption peak at the point corresponds to the stretching vibration peak of -OH in LNU-80-COOH, further indicating that the anhydride functional group in LNU-80 has been converted into a carboxyl group, indicating that LNU-80-COOH was successfully prepared.
[0053] Figure 2: Figure 2-1 and Figure 2-2 The figures show the nitrogen adsorption-desorption curves of the porous organic polymers LNU-80 and LNU-80-COOH synthesized in this invention. As can be seen from the figures, in the low-pressure region, the nitrogen adsorption capacity of both LNU-80 and LNU-80-COOH increases rapidly with increasing relative pressure (P / P0), indicating the presence of numerous micropores in the polymer structure. In the high-pressure region, the nitrogen adsorption-desorption curves of both polymers exhibit obvious hysteresis lines, which are classified as Type IV curves according to the IUPAC classification, indicating the presence of mesopores in the polymer structure. The specific surface areas of LNU-80 and LNU-80-COOH, calculated using the Brunauer-Emmet-Teller (BET) model, are 950.35 m². 2 g -1 and 798.11 m 2 g -1 The BET specific surface area of the polymer was significantly reduced after carboxyl modification, mainly due to the blockage of pores by some carboxyl functional groups after modification.
[0054] Figure 3: Figure 3-1 and Figure 3-2The images show the pore size distributions of the porous organic polymers LNU-80 and LNU-80-COOH synthesized in this invention. The pore size distributions of LNU-80 and LNU-80-COOH were evaluated using nonlocal density functional theory (NLDFT). The results show that the pore size of LNU-80 is mainly distributed in the range of 0.56–3.29 nm, while the pore size of LNU-80-COOH is continuously distributed between 0.79 and 18.57 nm, exhibiting hierarchical porous structure characteristics, primarily mesoporous. This may be due to the disruption of the skeletal structure between molecular chains during the alkalization process, resulting in an increase in pore size.
[0055] Figure 4: Figure 4-1 and Figure 4-2 The figures show the effect of pH on the zeta potential of the porous organic polymers LNU-80 and LNU-80-COOH synthesized in this invention. As can be seen from the figures, LNU-80 exhibits a positive zeta potential at pH < 3, and a negative potential at pH = 3~10. In contrast, LNU-80-COOH exhibits a more negative potential at pH = 10. This difference may be attributed to the loading of additional oxygen-rich functional groups on the polymer surface during the alkaline treatment process.
[0056] Figure 5 : Figure 5 The thermogravimetric spectra of the porous organic polymers LNU-80 and LNU-80-COOH synthesized in this invention are shown. As can be seen from the figures, the 10% weight loss temperatures of LNU-80 and LNU-80-COOH under nitrogen conditions are 374 °C and 331 °C, respectively, indicating that the polymers possess excellent thermal stability and are highly suitable for removing pollutants from water under harsh environmental conditions.
[0057] Example 3 Adsorption Experiment
[0058] Malachite green (MG), a cationic dye, was dissolved in distilled water to prepare a 2000 ppm stock solution. This stock solution was then diluted with distilled water to different initial concentrations using pipettes, and a series of adsorption experiments were conducted. To investigate the effect of pH on adsorption performance, adsorption experiments were performed within a pH range of 2–10. Before adding LNU-80-COOH, the pH of the malachite green solution was adjusted by adding 0.01 M NaOH and HNO3.
[0059] To evaluate the maximum adsorption capacity (Q) of LNU-80-COOH for malachite green... eIsothermal adsorption experiments were conducted. The experimental procedure was as follows: 2 mg of LNU-80-COOH was added to 20 mL of aqueous solutions containing different concentrations of malachite green (pH = 7), and the solutions were shaken at 25 ℃, 35 ℃, and 45 ℃ for 24 h to ensure adsorption equilibrium. The supernatant was collected, and the absorbance of malachite green at 617 nm was measured using a UV-Vis spectrophotometer. To study the adsorption selectivity of LNU-80-COOH for malachite green, calcein (Cal) and methyl orange (MO) were used as controls at pH = 7. 2 mg of polymer LNU-80-COOH was added to vials containing 20 mL of 100 ppm malachite green and the control dye, respectively. The solutions were stirred at 25 ℃, filtered at specified time intervals, and the supernatant was collected and measured using a UV-Vis spectrophotometer to calculate the removal rate of malachite green by LNU-80-COOH.
[0060] Figure 6: Figure 6-1 and Figure 6-2 The figures show the effect of pH on the adsorption performance of porous organic polymers LNU-80 and LNU-80-COOH. As shown, the adsorption capacity of the polymers for malachite green increases significantly with increasing pH from 2 to 10. Specifically, both polymers exhibit good adsorption performance at pH = 10, with a removal rate > 95%. This can be attributed to the electrostatic forces and π-π interactions between the positively charged dye molecules and the negatively charged adsorbent surface. Although both polymers show good removal rates at pH = 10, considering their application in real-world wastewater, subsequent studies were conducted at pH = 7.
[0061] Figure 7: Figure 7-1 and Figure 7-2 This figure shows the adsorption isotherms of malachite green for the porous organic polymer materials LNU-80 and LNU-80-COOH synthesized in this invention at 25 °C. As can be seen from the figure, both polymers are more suitable for the Langmuir adsorption model, indicating that the adsorption of malachite green by LNU-80 and LNU-80-COOH is monolayer adsorption. Furthermore, calculations using the Langmuir model show that the maximum adsorption capacities of LNU-80 and LNU-80-COOH at 25 °C are 3999 and 4398 mg g, respectively. -1 The performance difference is mainly attributed to the fact that the negative functional group (-OH) in LNU-80-COOH provides additional negative potential active sites, which can bind to the cationic dye malachite green through electrostatic interactions and hydrogen bonding interactions. In addition, the introduction of the carboxyl functional group effectively improves the water dispersibility of the polymer, thus exhibiting superior adsorption performance.
[0062] Figure 8 : Figure 8 This figure shows the adsorption isotherms of the porous organic polymer LNU-80-COOH synthesized in this invention for malachite green at 25 °C, 35 °C, and 45 °C. Based on the excellent adsorption performance of LNU-80-COOH at 25 °C, the adsorption isotherms of LNU-80-COOH for malachite green were tested at 35 °C and 45 °C, respectively. As can be seen from the figure, the adsorption capacity of LNU-80-COOH for malachite green increases further with the increase of the equilibrium concentration of malachite green. By comparing the adsorption capacity at 25 °C, 35 °C, and 45 °C, it can be found that high temperature is favorable for the adsorption of malachite green by LNU-80-COOH, indicating that the adsorption of the polymer is an endothermic process.
[0063] Figure 9 : Figure 9 This paper describes the effect of the porous organic polymer LNU-80-COOH synthesized in this invention on the adsorption of malachite green in water under the presence of different interfering ions. Actual wastewater contains not only organic pollutants but also a large amount of inorganic salts; therefore, different salt solution systems were selected to test the removal efficiency of LNU-80-COOH for malachite green. As can be seen from the figure, even under the condition of interfering ions, LNU-80-COOH still maintains good adsorption capacity for malachite green, exhibiting excellent adsorption selectivity.
[0064] Figure 10 : Figure 10 This paper describes the effect of the porous organic polymer LNU-80-COOH synthesized in this invention on the adsorption of malachite green in water under different salt concentrations. As can be seen from the figure, when the NaCl concentration is between 0 and 0.10 mol / L... -1 Within a certain range, the adsorption of malachite green by LNU-80-COOH was not significantly affected. This is because, on the one hand, the presence of an appropriate concentration of salt solution promotes the dissociation of dye molecules, which is beneficial to the adsorption of the adsorbent; on the other hand, the salting-out effect disrupts hydrogen bonds, thereby weakening the adsorption. The results show that the adsorption performance of malachite green by LNU-80-COOH did not change significantly with the increase of NaCl concentration, indicating that the effect of different salt solution ionic strengths on its adsorption is negligible.
[0065] Figure 11 : Figure 11 The porous organic polymer LNU-80-COOH synthesized in this invention is effective against malachite green (400 mg L) in different water bodies. -1The adsorption capacity of LNU-80-COOH is shown in the figure. The figure illustrates the differences in adsorption of the cationic dye malachite green by the adsorbent LNU-80-COOH under five real-world environments (containing distilled water dye solutions). As can be seen from the figure, the dye adsorption capacity increases to varying degrees in rainwater, tap water, seawater, and river water. These results indicate that LNU-80-COOH has excellent development potential in the field of pollutant removal in real-world aquatic environments.
[0066] Figure 12 : Figure 12 This study investigates the cyclic stability of the porous organic polymer LNU-80-COOH synthesized in this invention. As shown in the figure, after five cycles, the removal rate of malachite green only decreased from 99.3% to 93.7%. This slight decrease in removal rate may be due to incomplete release or deactivation of some active sites. In conclusion, this type of adsorbent material exhibits good cyclic stability and has broad application potential in the practical treatment of dye wastewater.
Claims
1. A carboxyl-functionalized porous organic polymer adsorbent, characterized in that, The structural formula is shown as formula (I), (Ⅰ)。 2. The method of claim 1, wherein the carboxyl-functionalized porous organic polymer adsorbent is prepared by the steps of: The preparation method of LNU-80 is as follows:
3. The method for preparing a carboxyl-functionalized porous organic polymer adsorbent according to claim 2, characterized in that, Step 1: under the condition of nitrogen, phenyl maleic anhydride and tetraphenylmethane are added into a double-neck flask; Step 2: after three vacuum-nitrogen circulation, dimethylformaldehyde FDA, anhydrous 1,2-dichloroethane are added, and stirring is performed; Step 3: after stirring, anhydrous FeCl3 is added into the mixture for reaction; Step 4: after the reaction is completed, filtration is performed, and the unreacted monomer and catalyst are removed through washing several times; Step 5: the obtained solid product is extracted by tetrahydrofuran, and vacuum drying is performed, so that the brown yellow powder is obtained as LNU-80. In step 3, the reaction is performed at 45 ℃ for 5 h, and then the temperature is increased to 80 ℃ for 19 h.
4. The method for preparing a carboxyl-functionalized porous organic polymer adsorbent according to claim 3, characterized in that, The heating reflux is performed at 100 °C for 24 h.
5. The method for preparing a carboxyl-functionalized porous organic polymer adsorbent according to claim 2, characterized in that, 6. Application of the carboxyl-functionalized porous organic polymer adsorbent in adsorbing cationic dye malachite green according to any one of claims 1-5. The method is as follows: in a solution of malachite green, the pH is adjusted to 2-10, the carboxyl-functionalized porous organic polymer adsorbent LNU-80-COOH according to any one of claims 1-5 is added, and the malachite green is subjected to oscillation adsorption at a temperature of 25-45 ℃.
7. Use according to claim 6, characterized in that, The pH is adjusted to 10.
8. Use according to claim 6, characterized in that, The temperature is 45 ℃.
9. Use according to claim 6, characterized in that,